Are we family? On the scientific connections between archivists and bibliologists, and information scientists - Monika Cołbecka (Folia Historica Cracoviensia)
In 1937, Marian Łodyński, a librarian and historian, published an article entitled “Archiwiści i bibliotekarze” (literally “Archivists and Librarians”) in Przegląd Biblioteczny journal. His text served as a pretext for a dispute initiated by Wojciech Hejnosz. It juxtaposed full opening of archives to users to the duty of preserving historical sources from destruction, and revealed differences in the perception of certain phenomena, yet primarily was a proof of mutual research interest. Although the ties between researchers operating in the disciplines in question were the strongest in the 1970s and 1980s, it seems that it is the first time ever that we have had so much in common. The dynamic democratisation of society, which requires accurate information promptly delivered by information institutions, has made a significant impact on the roles of archivists, librarians, and information scientists. Will we stand together in the face of these challenges, and do archivists draw from the achievements of related fields of study? The article presents considerations regarding the research problem thus formulated and the conclusions resulting from a study of scientific literature.